Response—Lawrence M. Friedman: Some Thoughts on the Relationship Between Law and Political Science - Lawrence M. Friedman (Washington University Law Quarterly, 1971)
The smug self-satisfaction of legal education retarded, for years, the interdisciplinary study of law. That self-satisfaction is now in process of retreat, and there is underway a serious movement to reform, recast, and revitalize legal education. There are two attacking armies: one from the clinical-activist side, and another from the social science side. The two forces are now allied, in rather uneasy coalition, against their joint enemy, the traditional forms of legal education. By rights, the two forces should remain good friends. But will they? It would not be the first time that allies fell out after a victory. In a law school dominated by clinical activists, what will become of social science? Will it be given a place of honor, or will it be thrown out (or exiled into other parts of the university), except insofar as it is willing to serve as a humble servant of the Pharaoh, making bricks for his temple? This possibility is real; it has some basis in the history and structure of legal education. The final outcome, only time can tell. Dr. Barker's introduction to the symposium takes a position, as I read it, of quiet optimism. He reads the testimony of events to say that a long, productive union of law and political science seems certain to sustain itself and grow. For the sake of both disciplines-and for the sake of the administration of justice, which would, in the long run, immeasurably gain-one hopes that events will bear him out.